Modification of the HeRO Graft Allowing Earlier Cannulation and Reduction in Catheter Dependent Days in Patients with End Stage Renal Disease: A Single Center Retrospective Review. (6th January 2014) - Hart, Deirdre; Gooden, Christie; Cummings, L. S.; Wible, Brandt C.; Borsa, John; Randall, Henry
Abstract : After creation of an arteriovenous fistula or placement of an arteriovenous graft, several weeks are required for maturation prior to first cannulation. Patients need an alternative way to receive hemodialysis during this time, frequently a catheter. After multiple failed access attempts, patients can run out of options and become catheter dependent. At our institution, we place HeRO grafts in eligible patients who have otherwise been told they would be catheter dependent for life. By combining the HeRO graft system with a Flixene graft, patients are able to remove catheters sooner or avoid placement as they can undergo cannulation for hemodialysis the next day. Utilizing this novel technique, twenty-one patients over a two-year period with various forms of central venous stenosis, catheter dependence, or failing existing arteriovenous access have been successfully converted to stable long term noncatheter based upper extremity access.